2006
DOI: 10.1002/masy.200651323
|View full text |Cite
|
Sign up to set email alerts
|

Natural Weathering Evaluation of LDPE‐Mango Starch Blends by Mechanical Properties and High Field NMR

Abstract: The low‐density polyethylene/mango starch blends were obtained and submitted a natural degradation. Their mechanical properties and structures changes were determined by tensile, low and high field nuclear magnetic resonance characterization after different weathering times. The exposition time and starch content could be correlated to the polymer matrix changes from void formation theories. The blend deformations were affected by the starch degradation time. The starch degradation, confirmed by nuclear magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Since synthetic polymers require longer weather exposure to study the effect of environmental degradation on these materials, when it comes to biodegradable polymers, this time becomes considerably shorter. Rodrigues et al (2006) produced blends with low-density polyethylene and up to 2% mango starch, which were subjected to natural degradation. The authors concluded that the starch content, as well as the exposure time, correlated with the formation of voids in the polymer matrix.…”
Section: Moreno Et Al (2022)mentioning
confidence: 99%
“…Since synthetic polymers require longer weather exposure to study the effect of environmental degradation on these materials, when it comes to biodegradable polymers, this time becomes considerably shorter. Rodrigues et al (2006) produced blends with low-density polyethylene and up to 2% mango starch, which were subjected to natural degradation. The authors concluded that the starch content, as well as the exposure time, correlated with the formation of voids in the polymer matrix.…”
Section: Moreno Et Al (2022)mentioning
confidence: 99%
“…Researches have been done to improve this polymer degradation process. Many studies were carried out to obtain blends with polysaccharides, like starch, for example [1,2], therefore only little improvement was obtained with these materials. Recently the development of new materials, in special polymeric nanocomposites, formed by polymer and layered silicates, have gained attention [3][4][5].…”
Section: Introductionmentioning
confidence: 99%